What Changes the Youth of Southeast Sulawesi (Indonesia) after Living Abroad - Kurrniawan Rachman, Muhammad (International Journal of Transdisciplinary Knowledge, 2021)
According to Central Bureau Statistic of Southeast Sulawesi, Indonesia, 24.15 % of citizens aged 7 until 24 years old decided to stop pursuing education. There have been many efforts to solve this problem, one of them is the effort of the country to send people to study abroad by scholarship or fellowship. This research tried to unveil the perspectives of people in Southeast Sulawesi who have experience studying or doing an internship abroad. The study used descriptive research providing open-ended questionnaires from fifty alumni of scholarships and fellowships from Southeast Sulawesi and it is analyzed by content analysis steps. In general, they showed positive feedback from the scholarship or fellowship experience they had. However, they perceived some critiques toward some cultures and system after returning to their homeland.